The Potential of Providing Chicken Manure in Improving Soil Health in Dry Lands - Safta, Laila; Fauzi, Taufik; Suwardji, Suwardji; Sudharmawan, A. A. Ketut; Mulyati, Mulyati (Jurnal Biologi Tropis, 2024)
Despite having a considerable potential area, the optimal utilization of dry land is challenging due to the generally low soil moisture content and fertility of dry land in Indonesia. This is evidenced by the intrinsically low organic matter content in dryland soils. Therefore, this article aims to provide information on the potential application of chicken manure to enhance soil fertility and health or to rehabilitate suboptimal dry lands in Indonesia. The methodology used in this article is qualitative, based on a literature review. One approach to improving the condition of dry land in Indonesia is the application of chicken manure, which acts as a soil conditioner and enhances overall soil fertility and health. The results of the study indicate that using chicken manure on dry land can increase crop production, thereby positively correlating with the profits of dry-land farmers.